Is Drought Caused by Fate? Analysis of Farmers’ Perception and Its Influencing Factors in the Irrigation Areas of GAP-Şanlıurfa, Turkey - Aydoğdu, Mustafa Hakkı; Cançelik, Mehmet; Sevinç, Mehmet Reşit; Çullu, Mehmet Ali; Yenigün, Kasım; Küçük, Nihat; Karlı, Bahri; Ökten, Şevket; Beyazgül, Uğur; Doğan, Hatice Parlakçı; Şahin, Zeliha; Mutlu, Nusret; et al. (MDPI AG, 2021)
This research aims to determine the belief-based drought perceptions and attitudes of farmers in Şanlıurfa, which is in a semi-arid climate regime, and the factors affecting them. The surveys were conducted through face-to-face interviews with farmers selected by a simple random sampling method in 2020. Analyses were performed with ordinal logit regression in STATA. According to the results, while the effects of settlement location, land size, age, and the size of the household were statistically significant to farmers seeing drought, which is the dependent variable, as caused by fate, the effects of income, experience, and education level were insignificant. For the probability of predicting drought for each independent variable in the sequence analysis, the highest probabilities were found among farmers in the Harran Plain, with 21–30 years of experience, from a household of one to four people, with the land area between 5.1 and 10.0 hectares, aged 61 and above, who were primary school graduates, and who had an annual income of less than 25,000 TL ($3561). The subject of drought should be given more place in religious education in the entire research area by prioritizing these groups. It would also be beneficial to organize workshops for the farmers by agricultural consultants, where Islamic scholars would be present to support science and knowledge in terms of faith. This study is the first in this context in Turkey and provides useful data to policymakers for drought-mitigation policies.
Keywords: faith; farmers’ perception; effective factors; Turkey; GAP-Şanlıurfa; climate change-based drought; 2. Zero hunger; 15. Life on land; 6. Clean water